Romanian foreign policy, the Republic of Moldova and the conflict in Transnistria 1990-2008 - Ana Maria Albulescu (CES Working Papers, 2023)
This article answers the following research question: What effects did Romanian Foreign Policy have on the settlement process in Transnistria between 1992 and 2008? By looking at this particular question this article conceptualizes the role of Romania towards the conflict in Transnistria. It identifies three different major changes in Romanian's Foreign Policy between 1990 and 2008 that include the following defining traits: post-communist identity( 1990-1993) ; re- defining of national identity (1993-2004) and defining an Euro-Atlantic identity (2004-2009). Based on this distinction three types of action towards the Republic of Moldova are identified: 1.Establishing Bilateral relations 2.Consolidation of diplomatic relations 3.Advocacy in Euro-Atlantic structures that have led to specific roles by Romania towards: 1.the facilitation of direct mediation (1992-1993) 2. Non- involvement in direct mediation and support for third party mediation (1993-2004) and 3. Support for the expansion of the third party mediation framework in the conflict in Transnistria (2004-2008).
Keywords: 330; foreign policy; Transnistrian conflict; mediation; Romania